Identifikasi Mikroorganisme Penyebab Otitis Media Supuratif Kronik Dan Kepekaannya Terhadap Antibiotik - Maya Rizky Amelia (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: Chronic suppurative otitis media (CSOM) is a chronic infection of the middle ear that has been in process for more than 2 months, which is characterized by perforation of the tympanic membrane and a continuous discharge or discharge arising from the ear canal. CSOM can be caused by a bacterial infection. In developing countries like Indonesia, the incidence of CSOM is quite high. Therefore, appropriate therapy is needed to overcome CSOM in Indonesia. Objective: To find out the most bacteria that cause CSOM and their sensitivity to antibiotics. Method: Using literature studies from national research journals by summarizing the topic of discussion and comparing the results presented in the article. Results: Proteus sp was found as the most common cause of CSOM in 2012, but only once was found in subsequent years. Bacteria that are commonly found as a whole are Staphylococcus sp, Pseudomonas sp, Streptococcus sp, and Klebsiella sp. Bacterial sensitivity to antibiotics from year to year there are changes. Antibiotics that have a high sensitivity to the bacteria that cause CSOM are Ciprofloxacin in almost all bacteria and meropenem for Pseudomonas sp. The sensitivity of Ciprofloxacin continues to decrease each year, by 100% in 2012 to 61.76% in 2016. Amoxicillin which was previously sensitive to several bacteria that cause CSOM in 2012, now has a high resistance especially against Pseudomonas sp which reaches 100%. Conclusion: Most bacteria that cause chronic suppurative otitis media (CSOM) are Pseudomonas sp and Staphylococcus sp. Antibiotics that have a high sensitivity to the bacteria that cause CSOM are Ciprofloxacin in almost all bacteria and meropenem for Pseudomonas sp. While Amoxicillin has a high resistance.